Amorphous solid electrolyte of sulfur oxide and preparation method and application thereof

CN123018106APending Publication Date: 2026-10-30TIANQI LITHIUM NEW ENERGY TECH RES (MEISHAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611196655.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

本发明提供的非晶态硫氧化物固体电解质的合成原料不使用昂贵的Li2S,大幅降低了原料成本。更重要的是,通过离子调控和工艺优化成功开发出兼具实用离子电导率、成本优势与工艺稳定性的非晶态硫氧化物固体电解质,该非晶态硫氧化物固体电解质表现出良好的(电)化学稳定性,具有良好的实用化前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018106A_ABST
    Figure CN123018106A_ABST
Patent Text Reader

Abstract

The application discloses an amorphous sulphur oxide solid electrolyte and a preparation method and application thereof. The amorphous sulphur oxide solid electrolyte comprises Li2O-P2S5-M x N y The amorphous sulphur oxide solid electrolyte is an amorphous sulphur oxide solid electrolyte, wherein M is one or more of Li, Al, Ga and Ta, N is one or more of F, Cl, Br, I, O and S, and the values of x and y satisfy 0 The amorphous sulphur oxide solid electrolyte developed by ion regulation and process optimization has practical ion conductivity, cost advantage and process stability, and has good (electro)chemical stability and good practical prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and more specifically, to an amorphous sulfur oxide solid electrolyte, its preparation method, and its application. Background Technology

[0002] In the field of all-solid-state battery technology, all-solid-state batteries using inorganic solid electrolytes are considered a key path to overcome the current technological bottlenecks of commercial liquid lithium-ion batteries due to their theoretically high safety, high energy density, and excellent electrochemical stability. They are expected to drive the upgrading and innovation of energy storage devices and equipment. Currently, mainstream inorganic solid electrolytes are mainly divided into three systems: oxides, sulfides, and halides. Among them, sulfide solid electrolytes have attracted widespread attention due to their room-temperature ionic conductivity comparable to that of liquid electrolytes.

[0003] However, traditional sulfide solid electrolytes still face numerous challenges in practical applications, hindering their industrialization. Specifically, on the one hand, their raw material costs are high. Conventional lithium sources heavily rely on high-purity Li₂S, and the synthesis process of Li₂S is complex and its purification is difficult, resulting in persistently high market prices. On the other hand, the purity and chemical stability of Li₂S compounds are easily affected by storage environment and time, leading to significant fluctuations in shelf life, which poses great difficulties for controlling the process stability and consistency of large-scale production. These factors together constitute the main obstacles to the industrialization of sulfide solid electrolyte technology. Summary of the Invention

[0004] The purpose of this invention is to overcome the problems existing in the prior art and to provide an amorphous sulfur oxide solid electrolyte, its preparation method and application.

[0005] The technical problem solved by this invention is achieved by the following technical solution.

[0006] This invention provides an amorphous sulfur oxide solid electrolyte, comprising Li₂O-P₂S₅-M x N y It is an amorphous sulfur oxide solid electrolyte, wherein M is one or more of Li, Al, Ga and Ta, N is one or more of F, Cl, Br, I, O and S, and the values ​​of x and y satisfy: 0 < x / y ≤ 1.

[0007] The present invention also provides a method for preparing the above-mentioned amorphous sulfur oxide solid electrolyte, comprising: ball milling and pressing the raw materials for preparing the sulfur oxide solid electrolyte under a protective gas atmosphere to obtain a sheet-like precursor, and then subjecting the sheet-like precursor to a programmed sintering heat treatment to obtain the amorphous sulfur oxide solid electrolyte.

[0008] The present invention also provides an application of the above-mentioned amorphous sulfur oxide solid electrolyte in a battery.

[0009] The present invention has the following beneficial effects: The amorphous sulfur oxide solid electrolyte provided by this invention does not use expensive Li₂S as a raw material, significantly reducing raw material costs. More importantly, through ion regulation and process optimization, an amorphous sulfur oxide solid electrolyte that combines practical ionic conductivity, cost advantages, and process stability has been successfully developed. This amorphous sulfur oxide solid electrolyte exhibits good (electro)chemical stability and has promising prospects for practical application. Attached Figure Description

[0010] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0011] Figure 1(a) shows the X-ray diffraction pattern of the amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-2LiBr prepared in Example 1 of the present invention; Figure 1(b) shows the EIS impedance spectrum of the amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-2LiBr prepared in Example 1 of the present invention; Figure 2(a) shows the X-ray diffraction pattern of the amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-2LiI prepared in Example 2 of the present invention; Figure 2(b) shows the EIS impedance spectrum of the amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-2LiI prepared in Example 2 of the present invention; Figure 3 The EIS impedance spectrum of the amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-1Ga2O3 prepared in Example 3 of this invention; Figure 4 The EIS impedance spectrum of the amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-1AlBr3 prepared in Example 4 of this invention; Figure 5(a) shows the X-ray diffraction pattern of the amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-1Al2O3 obtained in Example 5 of the present invention; Figure 5(b) shows the EIS impedance spectrum of the amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-1Al2O3 obtained in Example 5 of the present invention. Figure 6(a) shows the X-ray diffraction pattern of the amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-1As2S3 obtained in Example 6 of the present invention; Figure 6(b) shows the EIS impedance spectrum of the amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-1As2S3 obtained in Example 6 of the present invention. Detailed Implementation

[0012] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0013] The following is a detailed description of an amorphous sulfur oxide solid electrolyte, its preparation method, and its application, provided by embodiments of the present invention.

[0014] In a first aspect, the present invention provides an amorphous sulfur oxide solid electrolyte, comprising Li₂O-P₂S₅-M x N y It is an amorphous sulfur oxide solid electrolyte, wherein M is one or more of Li, Al, Ga and Ta, N is one or more of F, Cl, Br, I, O and S, and the values ​​of x and y satisfy: 0 < x / y ≤ 1.

[0015] This invention provides an amorphous sulfur oxide solid electrolyte that introduces lithium vacancies or interstitial lithium through elemental substitution to increase the lithium-ion carrier concentration. At the same time, it utilizes the radius difference between the dopant ions and the matrix ions to cause lattice distortion, widen the lithium-ion transport channels, and improve the ion conductivity of the electrolyte.

[0016] In some alternative embodiments, substances represented by the following general structural formula are included: αLi₂O-βP₂S₅-γM x N y ; Where M is one or more of Li, Al, Ga and Ta, N is one or more of F, Cl, Br, I, O and S, 60<α<80, 20<β<40, 0<γ≤20, 100≤α+β+γ≤120, 0<x / y≤1.

[0017] In some alternative embodiments, the amorphous sulfur oxide solid electrolyte has an ionic conductivity > 0.65 mS / cm.

[0018] Secondly, the present invention also provides a method for preparing the above-mentioned amorphous sulfur oxide solid electrolyte, comprising: ball milling and pressing the raw materials for preparing the sulfur oxide solid electrolyte under a protective gas atmosphere to obtain a sheet-like precursor, and then subjecting the sheet-like precursor to a programmed sintering heat treatment to obtain the amorphous sulfur oxide solid electrolyte.

[0019] The above-described method for preparing amorphous sulfur oxide solid electrolytes, without using expensive Li2S, focuses on elemental doping and process optimization to develop amorphous sulfur oxide solid electrolytes with practical ionic conductivity (>0.65 mS / cm) and excellent process stability in a green, efficient, and low-cost manner, thereby promoting the development and commercial application of all-solid-state battery technology.

[0020] In some optional implementations, the following steps are included: [The text abruptly ends here, likely due to an incomplete sentence or missing information.] x N y The mixture of the ball milling material and the ball milling beads is ball milled to obtain a precursor powder. The precursor powder is then pressed into tablets to obtain a sheet precursor. Under a protective gas atmosphere, the sheet precursor is subjected to programmed sintering heat treatment to obtain a sintered product. The sintered product is then cooled and ground to obtain an amorphous sulfur oxide solid electrolyte.

[0021] In some optional embodiments, the ball milling process is carried out under argon protection and includes pre-milling, primary ball milling, and secondary ball milling, wherein: the ball-to-material ratio of the pre-milling, primary ball milling, and secondary ball milling is 5-20:1; the rotation speed of the pre-milling is 100-300 rpm; the pre-milling time is 0.2-2 hrs; the rotation speed of the primary and secondary ball milling is 300-600 rpm; and the time of the primary and secondary ball milling is 10-60 hrs.

[0022] In some alternative embodiments, the pre-milling and primary ball milling of Li2O, P2S5, and M x N y The raw materials are θ%, δ%, and 100% of their respective stoichiometric ratios. During the second ball milling, (1-θ)% of Li2O and (1-δ)% of P2S5 raw materials are added, where 0≤θ≤1 and 0≤δ≤1.

[0023] In some optional embodiments, the programmed sintering heat treatment includes two parts: a primary sintering nucleation stage and a secondary sintering shaping stage. The primary sintering nucleation stage is performed at a temperature of 160-240°C for 0.5-5 hours, while the secondary sintering shaping stage is performed at a temperature of 240-320°C for 1-10 hours. The heating / cooling rate of the programmed sintering heat treatment is 2-10°C / min. Experimental results show that sintering temperature has a competitive influence on intrinsic composition and conductivity: lower temperatures result in insufficient densification and high grain boundary resistance; higher temperatures induce the volatilization of active elements, causing the phase to deviate from the stoichiometry and generating lattice defects, increasing bulk resistivity. In this invention, through process optimization, the sintering temperature is strictly limited to the highest densification temperature range while avoiding decomposition and volatilization, thus balancing bulk phase and grain boundary conduction.

[0024] In some optional embodiments, the protective gas for the programmed sintering heat treatment includes one or more high-purity gases selected from helium (He), neon (Ne), argon (Ar), and nitrogen (N2); the flow rate of the protective gas for the programmed sintering heat treatment is controlled at 0-2 L / min.

[0025] Thirdly, the present invention also provides an application of the above-mentioned amorphous sulfur oxide solid electrolyte in a battery.

[0026] The present invention will be further described below with reference to embodiments.

[0027] Example 1: This embodiment provides an amorphous sulfur oxide solid electrolyte with the general structural formula 70Li₂O-30P₂S₅-2LiBr. The synthesis process is as follows: In an argon-filled glove box (water content ≤ 0.1 ppm, oxygen content ≤ 0.1 ppm), calculate the required mass of raw materials based on the stoichiometric ratio of the target structural formula. Weigh out 100% Li2O, 50% P2S5, and 100% LiBr respectively and transfer them to a zirconia ball mill jar. Fill the jar with zirconia grinding beads at a ball-to-material ratio of 20:1. The diameter of the grinding beads ranges from 3 to 12 mm. Seal the ball mill jar.

[0028] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). Pre-milling was performed at 150 rpm for 1 hour, followed by a primary ball milling at 500 rpm for 10 hours. The material adhering to the walls of the ball mill jar was then transferred to a glove box to remove the remaining material to the bottom. The remaining 50% of P2S5 was weighed and transferred to the ball mill jar. After sealing, the ball mill jar was transferred to the high-energy ball mill for a secondary ball milling at 500 rpm for 10 hours. The initially obtained precursor powder was then collected and pressed into tablets using a mold.

[0029] The sheet-like precursor was subjected to programmed sintering heat treatment in a ventilated tubular furnace or a muffle furnace under atmosphere protection. The first sintering nucleation temperature was 210℃, and the annealing time was 0.58hr; the second sintering nucleation temperature was 260℃, and the annealing time was 1.17hr; after which it was cooled to room temperature, with a heating rate of 2℃ / min, a cooling rate of 2℃ / min, and a high-purity argon gas flow rate of 0.5L / min.

[0030] The harvested material was then ground and refined to obtain an amorphous sulfur oxide solid electrolyte, 70Li₂O-30P₂S₅-2LiBr, suitable for all-solid-state batteries. As shown in Figure 1(a), this material did not produce obvious characteristic diffraction peak intensities, exhibiting clear amorphous characteristics. As shown in Figure 1(b), the EIS impedance curve measured using 200 mg of this material at 350 MPa shows that it has an ionic conductivity of 1.2 mS / cm.

[0031] Example 2: This embodiment provides an amorphous sulfur oxide solid electrolyte with the general structural formula 70Li₂O-30P₂S₅-2LiI. The synthesis process is as follows: In an argon-filled glove box (water content ≤ 0.1 ppm, oxygen content ≤ 0.1 ppm), calculate the required mass of raw materials based on the stoichiometric ratio of the target structural formula. Weigh out 100% Li2O, 50% P2S5, and 100% LiI respectively and transfer them to a zirconia ball mill jar. Fill the jar with zirconia grinding beads at a ball-to-material ratio of 20:1. The diameter of the grinding beads ranges from 3 to 12 mm. Seal the jar.

[0032] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). Pre-milling was performed at 150 rpm for 1 hour, followed by a primary ball milling at 500 rpm for 10 hours. The material adhering to the walls of the ball mill jar was then transferred to a glove box to remove the remaining material to the bottom. The remaining 50% of P2S5 was weighed and transferred to the ball mill jar. After sealing, the ball mill jar was transferred to the high-energy ball mill for a secondary ball milling at 500 rpm for 10 hours. The initially obtained precursor powder was then collected and pressed into tablets using a mold.

[0033] The sheet-like precursor was subjected to programmed sintering heat treatment in a ventilated tubular furnace or a muffle furnace under atmosphere protection. The first sintering nucleation temperature was 210℃, and the annealing time was 0.58hr; the second sintering nucleation temperature was 260℃, and the annealing time was 1.17hr; after which it was cooled to room temperature, with a heating rate of 2℃ / min, a cooling rate of 2℃ / min, and a high-purity argon gas flow rate of 0.5L / min.

[0034] The harvested material was then ground and refined to obtain an amorphous sulfur oxide solid electrolyte, 70Li2O-30P2S5-2LiI, suitable for all-solid-state batteries. As shown in Figure 2(a), this material did not produce obvious characteristic diffraction peak intensities, exhibiting a clear amorphous structure. As shown in Figure 2(b), the EIS impedance curve measured using 200 mg of this material at 350 MPa shows that it has an ionic conductivity of 1.29 mS / cm.

[0035] Example 3: This embodiment provides an amorphous sulfur oxide solid electrolyte with the general structural formula 70Li2O-30P2S5-1Ga2O3. The synthesis process is as follows: In an argon-filled glove box (water content ≤ 0.1 ppm, oxygen content ≤ 0.1 ppm), calculate the required mass of raw materials based on the stoichiometric ratio of the target structural formula. Weigh out 100% Li2O, 60% P2S5, and 100% Ga2O3 respectively and transfer them to a zirconia ball mill jar. Fill the jar with zirconia grinding beads at a ball-to-material ratio of 20:1. The diameter of the grinding beads ranges from 3 to 12 mm. Seal the ball mill jar.

[0036] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7 model). Pre-milling was performed at 150 rpm for 1 hour, followed by a primary ball milling at 500 rpm for 10 hours. The material adhering to the walls of the ball mill jar was then transferred to a glove box to remove the remaining material to the bottom. The remaining 40% of P2S5 was weighed and transferred to the ball mill jar. After sealing, the ball mill jar was transferred to the high-energy ball mill for a secondary ball milling at 500 rpm for 10 hours. The initially obtained precursor powder was then collected and pressed into tablets using a mold.

[0037] The sheet-like precursor was subjected to programmed sintering heat treatment in a ventilated tubular furnace or a muffle furnace under atmosphere protection. The first sintering nucleation temperature was 210℃, and the annealing time was 0.5hr; the second sintering nucleation temperature was 260℃, and the annealing time was 1hr; then it was cooled to room temperature, with a heating rate of 2℃ / min, a cooling rate of 2℃ / min, and a high-purity argon gas flow rate of 0.5L / min.

[0038] The harvested material was then ground and refined to obtain an amorphous sulfur oxide solid electrolyte, 70Li₂O₃-30P₂S₅-1Ga₂O₃, suitable for all-solid-state batteries. Figure 3 As shown, the EIS impedance curve obtained using 200 mg of this material at 350 MPa shows that it has an ionic conductivity of 1.42 mS / cm.

[0039] Example 4: This embodiment provides an amorphous sulfur oxide solid electrolyte with the general structural formula 70Li2O-30P2S5-1AlBr3. The synthesis process is as follows: In an argon-filled glove box (water content ≤ 0.1 ppm, oxygen content ≤ 0.1 ppm), calculate the required mass of raw materials based on the stoichiometric ratio of the target structural formula. Weigh out 100% Li2O, 40% P2S5, and 100% AlBr3 respectively and transfer them to a zirconia ball mill jar. Fill the jar with zirconia grinding beads at a ball-to-material ratio of 20:1. The diameter of the grinding beads ranges from 3 to 12 mm. Seal the jar.

[0040] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). Pre-milling was performed at 150 rpm for 1 hour, followed by a primary ball milling at 500 rpm for 10 hours. The material adhering to the walls of the ball mill jar was then transferred to a glove box to remove it to the bottom. The remaining 60% of P2S5 was weighed and transferred to the ball mill jar. After sealing, the ball mill jar was transferred to the high-energy ball mill for a secondary ball milling at 500 rpm for 10 hours. The initially obtained precursor powder was then collected and pressed into tablets using a mold.

[0041] The sheet-like precursor was subjected to programmed sintering heat treatment in a ventilated tubular furnace or a muffle furnace under atmosphere protection. The first sintering nucleation temperature was 210℃, and the annealing time was 0.5hr; the second sintering nucleation temperature was 260℃, and the annealing time was 1hr; then it was cooled to room temperature, with a heating rate of 2℃ / min, a cooling rate of 2℃ / min, and a high-purity argon gas flow rate of 0.5L / min.

[0042] The harvested material was then ground and refined to obtain an amorphous sulfur oxide solid electrolyte, 70Li₂O-30P₂S₅-1AlBr₃, suitable for all-solid-state batteries. Figure 4 As shown, the EIS impedance curve obtained using 200 mg of this material at 350 MPa shows that it has an ionic conductivity of 1.57 mS / cm.

[0043] Example 5: This embodiment provides an amorphous sulfur oxide solid electrolyte with the general structural formula 70Li2O-30P2S5-1Al2O3. The synthesis process is as follows: In an argon-filled glove box (water content ≤0.1ppm, oxygen content ≤0.1ppm), weigh Li2O, P2S5, and Al2O3 according to the stoichiometric ratio, then transfer them to a zirconia ball mill jar. Fill the jar with zirconia grinding beads at a ball-to-material ratio of 20:1. The diameter of the grinding beads should be 3-12mm. Finally, seal the grinding jar with a lid.

[0044] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). A first ball milling was performed at 150 rpm for 1 hour, followed by a cleaning of the milled material. A second ball milling was performed at 500 rpm for 20 hours. The resulting precursor powder was then collected and pressed into tablets using molds.

[0045] The sheet-like precursor was subjected to programmed annealing in a vented tubular furnace or a muffle furnace under atmosphere protection. The annealing temperature during the preheating stage was 210℃, and the annealing time was 0.5hr; the annealing temperature during the shaping stage was 260℃, and the annealing time was 1hr; it was then cooled to room temperature, with a heating rate of 5℃ / min, a cooling rate of 8℃ / min, and a high-purity argon gas flow rate of 0.4L / min.

[0046] The harvested material was then ground and refined to obtain an amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-1Al2O3. As shown in Figure 5(a), this material did not produce obvious characteristic diffraction peak intensities, exhibiting obvious amorphous structural characteristics. As shown in Figure 5(b), the EIS impedance curve measured using 150 mg of this material at 350 MPa shows that it has an ionic conductivity of 0.95 mS / cm, and also exhibits good densification properties.

[0047] Example 6: This embodiment provides an amorphous sulfur oxide solid electrolyte with the general structural formula 70Li2O-30P2S5-1As2S3. The synthesis process is as follows: In an argon-filled glove box (water content ≤0.1ppm, oxygen content ≤0.1ppm), weigh Li2O, P2S5, and As2S3 according to the stoichiometric ratio, then transfer them to a zirconia ball mill jar. Fill the jar with zirconia grinding beads at a ball-to-material ratio of 20:1. The diameter of the grinding beads should be 3-12mm. Finally, seal the jar.

[0048] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). A first ball milling was performed at 150 rpm for 1 hour, followed by a cleaning of the milled material. A second ball milling was performed at 500 rpm for 20 hours. The resulting precursor powder was then collected and pressed into tablets using molds.

[0049] The sheet-like precursor was subjected to programmed annealing in a vented tubular furnace or a muffle furnace under atmosphere protection. The annealing temperature during the preheating stage was 210℃, and the annealing time was 0.5hr; the annealing temperature during the shaping stage was 260℃, and the annealing time was 1hr; it was then cooled to room temperature, with a heating rate of 5℃ / min, a cooling rate of 8℃ / min, and a high-purity argon gas flow rate of 0.4L / min.

[0050] The harvested material was then ground and refined to obtain an amorphous sulfur oxide solid electrolyte 70Li2O-30P2S5-1As2S3. As shown in Figure 6(a), this material did not produce obvious characteristic diffraction peak intensities, exhibiting obvious amorphous structural characteristics. As shown in Figure 6(b), the EIS impedance curve measured using 150 mg of this material at 350 MPa shows that it has an ionic conductivity of 0.65 mS / cm, and also exhibits good densification properties.

[0051] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. An amorphous sulfur oxide solid electrolyte, characterized in that, Including Li2O-P2S5-M x N y It is an amorphous sulfur oxide solid electrolyte, wherein M is one or more of Li, Al, Ga and Ta, N is one or more of F, Cl, Br, I, O and S, and the values ​​of x and y satisfy: 0 < x / y ≤ 1.

2. The amorphous sulfur oxide solid electrolyte according to claim 1, characterized in that, This includes substances represented by the following general structural formulas: αLi2O-βP2S5-γM x N y ; Where M is one or more of Li, Al, Ga and Ta, N is one or more of F, Cl, Br, I, O and S, 60<α<80, 20<β<40, 0<γ≤20, 100≤α+β+γ≤120, 0<x / y≤1.

3. The amorphous sulfur oxide solid electrolyte according to claim 1, characterized in that, The ionic conductivity of the amorphous sulfur oxide solid electrolyte is >0.65 mS / cm.

4. A method for preparing an amorphous sulfur oxide solid electrolyte according to any one of claims 1-3, characterized in that, It includes: under a protective gas atmosphere, ball milling and pressing the raw materials for preparing sulfur oxide solid electrolyte to obtain a sheet-like precursor, and then subjecting the sheet-like precursor to a programmed sintering heat treatment to obtain the amorphous sulfur oxide solid electrolyte.

5. The preparation method according to claim 4, characterized in that, Includes the following steps: It will contain Li2O, P2S5, and M x N y The mixture of the ball milling material and the ball milling beads is ball milled to obtain a precursor powder. The precursor powder is then pressed into tablets to obtain a sheet precursor. Under a protective gas atmosphere, the sheet precursor is subjected to programmed sintering heat treatment to obtain a sintered product. The sintered product is then cooled and ground to obtain the amorphous sulfur oxide solid electrolyte.

6. The preparation method according to claim 5, characterized in that, The ball milling process is carried out under argon protection and includes pre-milling, primary ball milling, and secondary ball milling. The ball-to-material ratio of the pre-milling, primary ball milling, and secondary ball milling is 5-20:

1. The rotation speed of the pre-milling is 100-300 rpm, and the pre-milling time is 0.2-2 hours. The rotation speed of the primary and secondary ball milling is 300-600 rpm, and the time of the primary and secondary ball milling is 10-60 hours.

7. The preparation method according to claim 6, characterized in that, The pre-milled and first ball-milled Li2O, P2S5, M x N y The raw materials are θ%, δ%, and 100% of their respective stoichiometric ratios. During the second ball milling, (1-θ)% of Li2O and (1-δ)% of P2S5 raw materials are added, where 0≤θ≤1 and 0≤δ≤1.

8. The preparation method according to claim 5, characterized in that, The programmed sintering heat treatment includes two parts: primary sintering nucleation and secondary sintering shaping. The primary sintering nucleation temperature is 160-240℃ and the treatment time is 0.5-5hrs. The secondary sintering shaping temperature is 240-320℃ and the treatment time is 1-10hrs. The heating / cooling rate of the programmed sintering heat treatment is 2-10℃ / min.

9. The preparation method according to claim 8, characterized in that, The protective gas for the programmed sintering heat treatment includes one or more high-purity gases selected from helium (He), neon (Ne), argon (Ar), and nitrogen (N2); the flow rate of the protective gas for the programmed sintering heat treatment is controlled at 0-2 L / min.

10. The application of the amorphous sulfur oxide solid electrolyte according to any one of claims 1-3 or the amorphous sulfur oxide solid electrolyte prepared by the preparation method according to any one of claims 4-9 in a battery.